2008
DOI: 10.7202/018663ar
|View full text |Cite
|
Sign up to set email alerts
|

Santé mentale des sans-abri : faut-il intervenir davantage ?

Abstract: 40 % des personnes sans domicile fixe de Montréal souffrent d’un trouble mental grave. Cette situation alarmante a des causes complexes. Prises isolément, aucune ne peut prétendre tout expliquer. Parmi elles, l’état actuel du droit interpelle plus particulièrement les psychiatres et les juristes dans leur devoir de protéger les personnes les plus démunies. En effet, on ne peut plus se contenter d’invoquer la désinstitutionnalisation pour expliquer la forte proportion de malades mentaux parmi les itinérants. Il… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…Nous savons effectivement que les personnes sans-abri sont davantage sujettes aux troubles mentaux. « 40 % des personnes sans domicile fixe de Montréal souffrent d'un trouble mental grave » (Dubreucq, 2008). En Île-de-France, un tiers des sans domicile fixe souffraient, en 2009, de troubles psychiatriques sévères (troubles psychotiques, troubles sévères de l'humeur et troubles anxieux).…”
Section: Une Fragilité Psychique Plus Importanteunclassified
“…Nous savons effectivement que les personnes sans-abri sont davantage sujettes aux troubles mentaux. « 40 % des personnes sans domicile fixe de Montréal souffrent d'un trouble mental grave » (Dubreucq, 2008). En Île-de-France, un tiers des sans domicile fixe souffraient, en 2009, de troubles psychiatriques sévères (troubles psychotiques, troubles sévères de l'humeur et troubles anxieux).…”
Section: Une Fragilité Psychique Plus Importanteunclassified
“…[8][9][10][11] For instance, in Montreal, the Canadian Institute for Health Information has demonstrated that 40% of homeless persons suffer from severe mental health disorders. 12 Additionally, the health inequalities faced by homeless people constitute an important policy issue at local and national political levels and in connection with the co-ordination between social and health-care services. 13,14 Homeless persons indeed have multiple, complex and interrelated needs that require a broad range of housing, welfare and health services.…”
Section: Homelessness As a Public Health Concernmentioning
confidence: 99%
“…In addition, homeless persons present a high rate of substance abuse and suicidal ideation and behaviour . For instance, in Montreal, the Canadian Institute for Health Information has demonstrated that 40% of homeless persons suffer from severe mental health disorders . Additionally, the health inequalities faced by homeless people constitute an important policy issue at local and national political levels and in connection with the co‐ordination between social and health‐care services .…”
Section: Introductionmentioning
confidence: 99%